Management of a Complicated Ruptured Infected Pseudoaneurysm of the Femoral Artery in a Drug Addict - Emmanouil Psathas; Stella Lioudaki; Fotios-Filippos Karantonis; Petros Charalampoudis; Othon Papadopoulos; Chris Klonaris (Case Reports in Vascular Medicine)
Infected pseudoaneurysm of the femoral artery represents a devastating complication of intravenous drug abuse, especially in the event of rupture. Operative strategy depends upon the extent of arterial injury and the coexistence of infection or sepsis. Options range from simple common femoral artery (CFA) ligation to complex arterial reconstruction with autologous grafts (arterial, venous, or homografts). We report herein the management of a 29-year-old male patient who was urgently admitted with a ruptured pseudoaneurysm of the right CFA, extending well above the inguinal ligament. Multidisciplinary approach with multiple arterial reconstructions and subsequent coverage of the tissue defect with a rectus abdominis musculocutaneous flap transposition was performed.